Advences in the study of hypercholesterolemia and hypertriglyceridemia level in a population residing in the north-eastern region of Algeria. - Kara Nabila (International Journal of Computational and Experimental Science and Engineering, 2026)
Dyslipidaemia is a major public health concern worldwide. No data have been conducted in the north-eastern region of Algeria. The aim is to determine the prevalence of hypercholesterolemia and triglyceridemia by age group and gender. This descriptive, cross-sectional study used biochemical analysis reports from two private laboratories between December 2023 and December 2024. The medical records included lipid profile parameters such as total cholesterol (TC) and triglycerides (TG). The study population consisted of 3000 participants, 1051 (35%) of whom were men and 1949 (65%) of whom were women. The mean age of the men was 51,82 ± 14,97, while the mean age of the women was 53,99 ± 15,59. In this study, our population was divided into two age groups: Under 40 years (n = 615; 20.5%) and over 40 years (n = 2385; 79,5%). Dyslipidaemia was defined as having a total cholesterol level of more than or equal to 2 g/L (5,2 mmol/L) and triglyceride levels of more than or equal to 1,5 g/L (1,7 mmol/L).The mean total cholesterol level was higher in women (1,76 ± 0,43 g/L) than in men (1,52 ± 0,39 g/L) (p < 0.001). A normal total cholesterol level was significantly more common in women than in men (87,6% vs 72,3%, p<0.001). The mean triglyceride level was higher in men (1,44 ± 1,04 g/L) than in women (1,28 ± 0,72 g/L). Only 67,9 % of men and 71,3% of women had normal triglyceride levels (p < 0,001). Hypercholesterolemia was present in 12,4% (130/1051) of males and 27,7% (539/1949) of females (p = 0,15). Hypertriglyceridemia had a prevalence of 32,1% (337/1051) and 28,7% (560/1449) in males and females, respectively (p < 0.001). Our research has revealed that hypertriglyceridemia is highly prevalent in the study area, constituting a significant health concern associated with factors such as age and gender.